Carbon Accounting Tools for Sustainable Land Management - Toudert, Anass; Braimoh, Ademola; Bernoux, Martial; St-Louis, Maylina; Abdelmagied, Manar; Bockel, Louis; Ignaciuk, Adriana; Zhao, Yuxuan (World Bank, Washington, DC, 2018)
Agriculture, Forestry, and Other Land Use (AFOLU) sector is unique among economic sectors because its mitigation potential derives from both an enhancement of removals of GHGs and a reduction of emissions through management of land and livestock. The AFOLU sector is responsible for just under a quarter (approximately 10–12 GtCO2eq per year) of global anthropogenic GHG emissions, mainly due to deforestation and agricultural emissions from livestock, soil, and nutrient management. AFOLU emissions could change substantially in transformational pathways, given the high mitigation potential from agriculture, forestry, and bioenergy. Mitigation options in the AFOLU sector, therefore, need to be assessed, as far as possible, for their potential impact on all other services generated by land.